Agreement and Its Failures - Preminger, Omer, 1976- (Book collections on Project MUSE., 2014)
This monograph shows that the typically obligatory nature of predicate-argument agreement in phi-features (phi-agreement) cannot be captured through 'derivational time-bombs' - elements of the initial representation that cannot be part of a well-formed, end-of-the-derivation structure, and which are eliminated by the application of phi-agreement itself. This includes, but is not limited to, the 'uninterpretable features' of Chomsky 2000, 2001. Instead, it requires recourse to an operation - one whose invocation is obligatory, but whose successful culmination is not enforced by the grammar.